Character and Morals Education in Era 4.0 - Herawati, Susi; Aprison, Wedra; Mudinillah, Adam; Trisoni, Ridwal; Eliwatis, Eliwatis; Maimori, Romi (Yayasan Minang Darussalam, 2022)
The era of the industrial revolution 4.0 is a necessity, which forces all parties to take the benefits provided and minimize the negative impacts that arise. The era of the Industrial Revolution 4.0 has a not simple impact. It impacts all aspects of human life. Where the education system leads to the field of technology, it is very important the role of educators in improving the character of students so that they do not deviate from religious values. This study aims to find out an overview of the concept of character and moral education in the 4.0 period in students. This research method uses a qualitative method with a descriptive content analysis study model. The analysis is carried out on international, national, or similar books or articles related to character and moral education. It is clear the difference between morals and ethics, morals and character, where the differences come from “sources, scopes, traits, figures”. Character education is a system of instillation of character values that includes components of knowledge, awareness or will, and actions to carry out life values, both towards God, oneself, fellow human beings, nature, and the environment, as well as nationality to become a human being with a noble character.